THE ECONOMIC IMPACT OF TRIBAL GAMING ON NON-NATIVE COMMUNITIES IN OKLAHOMA USING L.O.S.T. DATA - Pembrook, Trent (My University, 2017)
Econometric analysis of tribal gaming on non-Native communities in Oklahoma. The study utilizes Local Option Sales Tax data as the outcome variable in a difference-in-difference model to analyze gaming impacts. Ten case study communities were selected from five micro-economies, one urban and one rural. Matching control communities were selected for each case study. The study analyzes a ten year timeframe, five years pre- and post- implementation, for treatment and control communities. The regression results were analyzed using Analysis of Variance statistics to determine tribal gaming impacts.
Keywords: Native American Studies.; Economics, General.; Business Administration, General.